Individualization as an Ambition: Mapping the Dating Landscape in Beijing. (November 2014) - Wang, Xiying; Nehring, Daniel
This article considers cultural hierarchies that may shape practices of dating and partner choice among young women and men in contemporary Beijing. Our research is mainly based on 43 in-depth interviews conducted in Beijing over the past six years. The distinction between Beijingers and waidiren (lit., outsiders) here serves as a framework to examine the cultural and socioeconomic differentiation of dating practices. We further complicate this framework by highlighting the internal heterogeneity of waidiren, including four groups: college students, New Beijingers, young professionals without Beijing hukou, and rural migrant laborers. We argue that our participants' narratives reflect a desire for autonomous partner choice and fulfilling love relationships; we also demonstrate how the hukou system, competition in the neoliberal market place, differential access to education, and the rural-urban division may interact to create opportunities and obstacles for young people's personal choices. Drawing on recent work by Yan Yunxiang (2009, 2010), our analysis further substantiates arguments about the individualization of contemporary Chinese society.